Design de ligas multicomponentes do sistema Ti-V-Nb-M (M = Cr, Co E Ni) para armazenagem de hidrogênio - SIlva, Bruno Hessel (2023)
Body Centered Cubic (BCC) multicomponent alloys have gained attention in the research of materials for H2 storage. These alloys have the potential to optimize H2 storage properties via compositional control. However, the investigation of the various storage properties is still scarce for these alloys, and the comprehension of hydrogenation reactions is in the early stages. Based on these challenges, this doctoral project aimed to: 1) Investigate the effect of the addition of non-hydride forming elements (M = Cr, Co and Ni) on the hydrogen storage properties and microstructure of multicomponent alloys of the Ti-V-Nb-M system; 2) Identify the formation of possible hydrides and structural changes caused by absorption/desorption reactions; 3) Design alloys of the Ti-V-Nb-M system with different storage properties for various applications. The hydrogen storage experiments, such as pressure-composition-temperature (PCT) diagrams, kinetics of absorption and partial hydrogenation, combined with detailed structural characterizations, allowed us to identify that the alloys absorb H initially forming an intermediate BCC hydride followed by the formation of a face-centered cubic (CFC) hydride reaching storage capacities of 2.4-3.2 wt%. The addition of non-hydride forming elements has been shown to contribute to the formation of secondary phases such as Laves C15 phase. Additionally, it showed influence on the thermodynamics of the CFC hydride formation (increasing the content of these elements results in higher equilibrium pressures for H absorption/desorption). The results also indicated that this influence is related to the valence electron concentration (VEC) of the alloys. Finally, computational thermodynamic tools proved to be excellent tools for the design of alloys with excellent storage properties. These tools allowed the obtention of the Ti11V30Nb28Cr31 BCC alloy with reversible absorption/desorption capacity of 1.7 wt%. of hydrogen at room temperature.